Understanding the acceptance of multisided teleconsultation platforms: a critical analysis and proposal of a theorical model - Galegale, Gustavo Perri (2023)
Teleconsultation gained substantial traction after the COVID-19. The ability to have healthcare services anywhere, anytime, saved thousands of lives in the process. One important aspect to scale teleconsultation is using multisided platforms. Multisided platforms create value by matchmaking two or more different sides, patients, doctors, nurses and other healthcare professionals and players, so that a consult can happen remotely. Several barriers and risks are present in such arrangement, ranging from technology risks on the capacity of the participants to use the software to access the platform, how the costs work and payments are made and the best combination of participants. There is little research on how the elements of a multisided teleconsultation platform impacts the intention to use and recommend a platform to another patient. This thesis used a combination of quantitative methods, creating a PLS-SEM model and performing a Necessary Condition Analysis (NCA) to evaluate the relation between the constructs. Overall teleconsultation platforms are helpful extending the reach and capacity of healthcare delivery and has the power to improve the life of several patients.